2018–2019 Florida Citrus Production Guide: Plant Bugs, Chewing Insect Pests, Caribbean Fruit Fly, and Thrips - Philip A. Stansly; Michael E. Rogers; Lauren M. Diepenbrock (EDIS, 2018)
This 5-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. The insects listed in this section are generalist feeders for which citrus is not a preferred host. They are, therefore, only sporadic problems in Florida citrus. While these pests do not require routine treatment in all groves, periodic outbreaks can potentially have dramatic impact on tree health and/or productivity. Written by P. A. Stansly, M. E. Rogers, and L. M. Diepenbrock, and published by the Entomology and Nematology Department, May 2018.